Learning Assessment - Nordin, Mohamad Sahari; Zubairi, Ainol Madziah; Nik Abdul Rahman, Nik Suryani; Tunku Ahmad, Tunku Badariah; Mohd Noor, Zainab; Ibrahim, Mohd Burhan; Abdul Rahman, Zainurin; Othman, Joharry (Akademi Kepimpinan Pengajian Tinggi (AKEPT), 2013)
This chapter discusses learning assessment practices among academicians in Malaysian higher education institutions.